Hypercoagulability as Measured by Thrombelastography May Be Associated with the Size of Acute Ischemic Infarct—A Pilot Study - Adam Wiśniewski; Aleksandra Karczmarska-Wódzka; Joanna Sikora; Przemysław Sobczak; Adam Lemanowicz; Karolina Filipska; Robert Ślusarz (Diagnostics, 2021)
Background: Thromboelastography (TEG®) measures coagulation function in venous blood. Previous studies have reported that this device providing an integrated data on dynamics of clot formation may be useful for predicting clinical outcome in ischemic stroke. We investigated whether a hypercoagulability detected by thrombelastography may be associated with larger size of acute ischemic infarct. Methods: We included 40 ischemic stroke subjects with large artery atherosclerosis or small-vessel disease to a cross-sectional pilot study. Thrombelastography parameters related to time of clot formation (R- reaction time, K-clot kinetics), clot growth and strengthening (angle-alpha and MA-maximum amplitude) and lysis (Ly30) were performed within first 24 h after the onset of stroke. A volume of ischemic infarct was assessed on the basis of diffusion-weighted imaging (DWI) sequence of magnetic resonance imaging. Results: In the entire group, we reported that subjects with a large ischemic focus (>2 cm3) had a higher diameter of a clot (measured as MA) than subjects with a small ischemic focus (p = 0.0168). In the large artery atherosclerosis subgroup, we showed a significant correlation between MA and size of acute infarct (R = 0.64, p = 0.0138), between angle (alpha) and size of acute infarct (R = 0.55, p = 0.0428) and stroke subjects with hypercoagulability (MA > 69 mm) had significantly higher probability of a larger size of acute ischemic focus compared to normalcoagulable subjects (5.45 cm3 vs. 1.35 cm3; p = 0.0298). In multivariate logistic regression hypercoagulability was a predictor of a large size of ischemic infarct (Odds ratio OR = 59.5; 95% confidence interval (CI) 1.08–3558.8; p = 0.0488). Conclusions: We emphasized that thrombelastography, based on the parameters related to clot strength, may have clinical utility to identify the risk of the extensive ischemic infarct.